Analysis of Employee Satisfaction with Helpdesk Websites using Service Quality in Construction Companies - Muhamad Raka Fadilah; Yopi Handrianto (Information Technology and Systems, 2023)
In analyzing employee satisfaction with the website, the main problem is whether the quality of service provided by the building construction company's helpdesk website is adequate. This information involves asking about the extent to which the website can meet the needs and expectations of employees in obtaining the necessary help and information. Helpdesk is a service unit tasked with helping organizations solve problems related to information and communication technology (ICT). This research aims to determine how satisfied employees are with the helpdesk services available at Building Construction Companies and whether these services meet employee expectations. This research uses quantitative research methods, and data collection techniques are carried out using questionnaire surveys. The results obtained show that H1 means that there is a significant influence on user quality, such as in the dimensions of reliability (0.39), Responsiveness (0.42), and Assurance (0.28) on user satisfaction with the helpdesk service system. Meanwhile, the Empathy dimension (0.05) gets a small positive gap value, almost meeting expectations. For the Tangibles dimension (0.59), there is no significant influence on user quality, so these results are quite satisfactory for employee desires and the need to improve service quality on user satisfaction in the helpdesk service system. Factors that influence the effectiveness of a helpdesk system include technical aspects, time management, effective response, and system use. Tangible aspects, such as physical and visual attributes, negatively impact helpdesk effectiveness. Companies must ensure that the helpdesk provides timely and effective responses to meet employee needs. Companies must also ensure that the helpdesk is user-friendly and intuitive so that employees can easily understand and use the helpdesk.